The Effect of Fermentation of Papaya Sub on the Quality of Dangke (MILK PROCESSED PRODUCTS) - Nasir, Yusrianto (Universitas Sulawesi Barat, 2023)
Dangke is a processed dairy product which is a typical Indonesian food made traditionally by the Enrekang people. Dangke is made by heating fresh milk and adding it to a solution of papaya latex (Carica papaya) until the milk forms curds and whey. This study aims to determine the effect of fermented papaya latex (Carica papaya) on the quality of dangke (dairy products). This type of research is experimental research. This research is located at the Biology Laboratory of the Muhammadiyah University of Parepare. The research design was Completely Randomized Design (CRD) with 3 treatments and repetitions as many as 3 times. Data was obtained by observing and measuring the quality of dangke in the form of taste, texture and color of dangke. Data analysis was performed by performing analysis of variance (ANOVA) at level (0.05). The results showed that data analysis related to dangke taste obtained a value of 28.00 so that the fermentation of papaya latex (Carica papaya) affected the dangke taste. The dangke texture was obtained a value of 0 so that the fermentation of papaya latex (Carica papaya) had no effect on the dangke texture. The color of dangke obtained a value of 0 so that fermentation of papaya latex (Carica papaya) did not affect the color of dangke. Fermentation of papaya latex (Carica papaya) has an effect on dangke taste and has no effect on dangke texture and color.